Naming Natural and Cultural Tourism Objects in Medalsari Village, Karawang Regency - Suntoko Suntoko; Abduloh Abduloh; Tedi Purbangkara; Ahmad Abdul Karim; Sigit Widiatmoko (Indonesian Language Education and Literature, 2024)
This research was conducted to reveal the application of the Sapir-Whorf hypothesis in naming tourist attractions in Medalsari Village, Karawang Regency. The research applies a qualitative study design, ethnographic methods, and the umbrella of anthropolinguistic studies to uncover the naming story, meaning, and cultural values behind the naming of tourist attractions.  The research results reveal that the naming of natural and cultural tourism objects in Medalsari Village cannot be separated from the role of central figures who contribute to the development of the village. Several tourist attractions have changed names due to commercialization and efforts to revitalize local culture. The names were reconstructed as part of a strategy to attract tourist interest and support the market narrative. This naming process supports the Sapir-Whorf hypothesis, which emphasizes that language, culture, and ways of thinking are closely related to people's lives. This research contributes to promoting tourist attractions in Medalsari Village and helps develop teaching materials in higher education. Integrating teaching materials focused on local wisdom can build a learning atmosphere that is more inclusive, interactive, and in line with student needs.  Utilizing teaching materials that are close to students can improve the quality of learning and have an impact on student learning experiences.  Penamaan Objek Wisata Alam dan Budaya di Desa Medalsari Kabupaten KarawangPenelitian ini dilakukan untuk mengungkap penerapan hipotesis Sapir-Whorf dalam penamaan objek wisata di Desa Medalsari, Kabupaten Karawang. Penelitian menerapkan desain studi kualitatif, metode etnografi, serta payung kajian antropolinguistik untuk menganalisis nama, makna, serta nilai budaya di balik penamaan objek wisata.  Hasil penelitian mengungkap bahwa penamaan objek wisata alam dan budaya di Desa Medalsari tidak lepas dari peran tokoh-tokoh sentral yang berkontribusi dalam perkembangan desa. Beberapa objek wisata mengalami perubahan nama dikarenakan adanya komersialisasi dan upaya revitalisasi budaya lokal. Rekonstruksi nama-nama dilakukan sebagai bagian dari strategi untuk menarik minat wisatawan dan mendukung narasi pasar. Proses penamaan ini mendukung hipotesis Sapir-Whorf, yang menegaskan bahwa bahasa, budaya, dan cara berpikir saling berkaitan erat dengan kehidupan masyarakat. Penelitian ini turut andil mempromosikan objek wisata di Desa Medalsari serta berdaya guna dalam pengembangan materi ajar di perguruan tinggi. Pengintegrasian materi ajar berfokus pada kearifan lokal dapat membangun suasana belajar yang lebih inklusif, interaktif, dan sesuai dengan kebutuhan mahasiswa.  Pemanfaatan materi ajar yang dekat dengan mahasiswa dapat meningkatkan kualitas pembelajaran serta berdampak terhadap pengalaman belajar mahasiswa.